Legal Review of Information Technology on the Misuse of Domain Names for Online Gambling Activities in Indonesia - Puteri, Rheyna Wisnu (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The rapid development of information technology has opened up opportunities for cybercrime, with online gambling becoming one of the deep-rooted social and legal problems in Indonesia. This study aims to analyze the modes of utilization of national domain names in online gambling operations and evaluate the effectiveness of law enforcement in Indonesia, given that the use of national domains is often an attempt at pseudo-legalization and avoidance of blocking. Using qualitative methods with a normative juridical approach as well as literature study and case studies, this study focuses on applicable positive legal norms. The results show that national domains are exploited through domain hijacking, misuse of academic/government domains, and domain switching to maintain operations. Although the government has carried out massive blocking through Kominfo and PANDI, this solution is only temporary. The conclusion confirms that the most effective action is through multi-layered criminal law enforcement by the Indonesian National Police, which not only prosecutes perpetrators under the ITE Law and the Criminal Code, but also with the Money Laundering Criminal Act (TPPU), as in the 1Xbet case, which successfully seized hundreds of billions in assets and provided a deterrent effect, while also urging the need for fundamental improvements to the domain registration system and cyber surveillance by public institutions.